1984
DOI: 10.1007/bf00915722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of piroxicam on structure and function of joint cartilage

Abstract: In vitro experiments were performed on isolated articular chondrocytes under the influence of piroxicam. It was demonstrated that this non-steroidal anti-inflammatory agent affected neither cell proliferation nor the incorporation of 35SO4 into matrix macromolecules. Dogs were treated with piroxicam for 8 weeks. Morphological studies were performed on the tissues of the knee joints. Macroscopic and light microscopic investigations revealed no structural differences between the tissues (synovial membrane and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For instance, indomethacin has been reported to induce and aggravate degenerative changes in the joints of chicken (15), mice (10) and Man (13-14) but seems not to affect the cartilage cells of dogs (12). Piroxicam has been found to reduce the prevalence of spontaneous osteoarthritis in Cs7-Black mice (10) and increased chondrocyte metabolism in Wistar rats (17), but apparently had no effect on canine (12), porcine (8) or rabbit cartilage (16).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, indomethacin has been reported to induce and aggravate degenerative changes in the joints of chicken (15), mice (10) and Man (13-14) but seems not to affect the cartilage cells of dogs (12). Piroxicam has been found to reduce the prevalence of spontaneous osteoarthritis in Cs7-Black mice (10) and increased chondrocyte metabolism in Wistar rats (17), but apparently had no effect on canine (12), porcine (8) or rabbit cartilage (16).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental in vivo studies, examining the effects of NSAID on cartilage, demonstrated differences in cartilage structure and metabolism after exposure to the drug from between four and eight weeks (19,21,24,27,28,30). The patients in our study were treated with carprofen for an average of three months with a median treatment time of two months and a minimum of one month.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, long-term (2-year) in vivo stud ies conducted in OA in rats and mice have classified meloxicam aschondroneutral [29], Studies conducted on other NSAIDs have shown variable effects on chondroformation and PGEt formation that seem to be in fluenced by the animal species and experi mental models used [26, 30. 31], Piroxicam, which, like meloxicam, is derived from enolic acid, had no effect on proteoglycan synthesis in chondrocytes isolated from rabbit shoulder cartilage [12,32], or in porcine [32] or dog articular cartilage [26], Similarly, piroxicam did not affect proteoglycan metabolism in iso lated and monolayer cultured chondrocytes, and the synthetic activity or quality of proteo glycans was unaffected by the presence of piroxicam in the test system [33], However, other studies have shown that NSAIDs, such as acetylsalicylatc [ 10,28.32] and indomethacin [34], may depress proteoglycan synthesis in articular cartilage of OA patients. Further more, it has been observed that indomethacin adversely affects disease progression in pa tients with OA hip joints [31,[35][36][37], Others, such as piroxicam [26], have shown no appre ciable effect on proteoglycan synthesis in nor mal cartilage [ 13,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to gastrointestinal and renal tolerability problems, often associated with NSAID use, some NSAIDs have also been shown to affect cartilage synthesis negatively [9][10][11][12]. In particular, the effect of NSAIDs on proteoglycan synthesis by chondrocytes has been investigated.…”
Section: Introductionmentioning
confidence: 99%